2013
DOI: 10.1021/om400819p
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ruthenium(II) and Gold(I) NHC Complexes: Synthesis, Characterization, and Evaluation of Their Anticancer Properties

Abstract: The synthesis, characterization, and biological evaluation of novel Ru(II)-and Au(I)-N-heterocyclic carbenes is reported. The NHC-ruthenium(II) complexes (1−6) were synthesized by reacting the appropriately substituted imidazolium bromides with Ag 2 O, forming the NHC-silver bromide in situ followed by transmetalation with dimeric p-cymene ruthenium(II) dichloride. In an analogous manner the NHCgold(I) chloride complexes (NHC-Au(I)Cl) 7−9 were synthesized, utilizing dimethylsulfido gold(I) chloride as the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 44 publications
2
76
0
1
Order By: Relevance
“…Surprisingly ruthenium(II) benzimidazolylidene carbene complexes with inadequate cellular uptake 111a-c showed a little efficacy toward tumor cell growth at the highest studied concentration. The synthesis, characterization and biological evaluation of novel NHC-ruthenium(II) complexes 112, 113a-e ( Figure 12) have been reported by Tacke et al All the NHC-ruthenium(II) complexes were synthesized by reacting the appropriately substituted imidazoliumbromides with Ag 2 O, forming the NHC-silver bromide in situ followed by transmetalation with dimeric p-cymeneruthenium(II) dichloride [136]. The IC 50 values of the complexes 112 and 113a-e against the human cancer cell lines Caki-1 (renal) and MCF-7 (breast) have revealed moderateto-good results [136].…”
Section: Antimicrobial and Antitumor Activities Of Nhc-ruthenium Complexesmentioning
confidence: 96%
See 3 more Smart Citations
“…Surprisingly ruthenium(II) benzimidazolylidene carbene complexes with inadequate cellular uptake 111a-c showed a little efficacy toward tumor cell growth at the highest studied concentration. The synthesis, characterization and biological evaluation of novel NHC-ruthenium(II) complexes 112, 113a-e ( Figure 12) have been reported by Tacke et al All the NHC-ruthenium(II) complexes were synthesized by reacting the appropriately substituted imidazoliumbromides with Ag 2 O, forming the NHC-silver bromide in situ followed by transmetalation with dimeric p-cymeneruthenium(II) dichloride [136]. The IC 50 values of the complexes 112 and 113a-e against the human cancer cell lines Caki-1 (renal) and MCF-7 (breast) have revealed moderateto-good results [136].…”
Section: Antimicrobial and Antitumor Activities Of Nhc-ruthenium Complexesmentioning
confidence: 96%
“…[147] 109b 0.31 ± 0.08 A2780 [147] 109c 0.12 ± 0.02 A2780 [147] 109d 4.82 ± 0.12 A2780 [147] 109e 41.0 ± 8.2 A2780 [147] 109f 0.21 ± 0.05 A2780 [147] 109a 25.6 ± 5.5 A2780R [147] 109b 1.77 ± 0.04 A2780R [147] 109c 0.23 ± 0.02 A2780R [147] 109d 37.8 ± 7.8 A2780R [147] 109e >200 A2780R [147] 109f 1.10 ± 0.12 A2780R [147] 109a 435 ± 25 HEK [147] 109b 29.0 ± 1.8 HEK [147] 109c 1.80 ± 0.20 HEK [147] 109d 64.0 ± 6.1 HEK [147] 109e >200 HEK [147] 109f 1.85 ± 0.12 HEK [147] 110 0.06 ± 0.0076 A549 [148] 110 1.25 ± 0.12 HCT116 [148] 110 0.1 ± 0.032 MCF7 [148] 111a >100 MCF7 112 >500 Caki-1 [136] 112 >500 MCF-7 [136] 113a 94 ± 5 Caki-1 [136] 113a 80 ± 15 MCF-7 [136] 113b 93 ± 2 Caki-1 [136] 113b 19 ±1 MCF-7 [136] 113c 170 ± 20 Caki-1 [136] 113c 7.1 ± 1.2 MCF-7 [136] 113d 39 ± 5 Caki-1 [136] 113d 2.4 ± 0.7 MCF-7 [136] 113e 13 ± 2 Caki-1 [136] 113e 7.0 ± 1.2 MCF-7 [136] 1 Fish RH, Jaouen G. Bioorganometallic chemistry: structural diversity of organometallic complexes with bioligands and molecular recognition studies of several supramolecular hosts with biomolecules, alkali-metal ions, and organometallic pharmaceuticals. Organometallics 22 (11), 2166-2177 (2003).…”
Section: Financial and Competing Interests Disclosurementioning
confidence: 99%
See 2 more Smart Citations
“…Hackenberg et al reported on the anticancer activity of NHC-carbene analogues of auranofin in which the alkyl substituents on the carbene were specifically modified (Au-8) [122]. Cytotoxicity studies were encouraging especially in human MCF7 breast adenocarcinoma and Caki-1 skin carcinoma cells, in particular in comparison to analogues where either the carbene or the thioglucose ligands are replaced by chlorides.…”
Section: Carbene Glycoconjugatesmentioning
confidence: 99%